Voting in the Horizon of Contradictory Truths: A Praxeological View on General Elections in State-Socialist Contexts - Langenohl, Andreas (Stan Rzeczy, 2019)
Historical and political science research into the role and significance of elections in state-socialist societies points to the variety of functions that these elections fulfilled, notwithstanding their deficiency if compared to liberal democratic conceptions such as the legitimation of the political regime and the mobilisation and socialisation of the population. This paper takes a novel approach towards the social significance of state-socialist elections, arguing that they conveyed imaginary understandings of the societies and polities of which they were part. The concept of the imaginary is discussed in conversation with Charles Taylor, who argues that public social practices are informed by mostly latent “understandings” that render them subjectively meaningful in the first place. Referring to historical research on state-socialist elections, imaginary understandings are identified that pertain in particular to the relationship between officially proclaimed “truths” and unofficial positionings towards them.